Level of economic enterprise management competency of elected local officials in Anahawan and Hinundayan, Southern Leyte. - Abad, Ma. Imelda O. (Tacloban City Ma. Imelda Abad [and] Jane P. Victoria, 2010)
The Local Government Units (LGUs) are responsible for the proper management of "local public enterprises" (LPEs). These economic enterprises should be self-sustaining and should be able to generate incomes to cover administration and operations expenses; however, oftentimes these economic enterprises operate at a loss. The success and failure of some LGUs to sustain and maintain LPEs supports the need for conducting a research on the Level of Economic Enterprise Management Competency of Local Government Officials.
This study mainly aims to determine the level of economic enterprise management competency of elected local government officials in Anahawan and Hinundayan, Southern Leyte and to determine the relationship between the socio-demographic factors and the level of economic enterprise management competency of the elected local government officials.
This is a descriptive study that was designed as a complete enumeration survey involving all the twenty four elected municipal officials in both towns. The study was conducted in the locales, because of their typical rural municipal setting of the Philippines. The results could serve as reflections to similar towns in the country in terms of economic enterprises management. Three data gathering techniques were utilized which are the self-administered questionnaires, structures interviews and secondary data.
It was found out that the local government officials in Anahawan and Hinundayan perceived themselves to be very competent in terms of managing the economic enterprises in their respective municipalities. Only educational attainment among the four socio-demographic factors showed a significant relationship with the level of economic enterprise management competency.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science